Basic Accounting Training to Improve Financial Management of KSBI MSMEs - Wahyuni, Lidia; Aryati, Titik; Dizar, Shafrani; Adawiyah, Wiwik Robiatul; Hestiana, Neng; Salim, Agus (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s national economy, particularly in job creation and income distribution. However, most MSME actors still face challenges in financial management due to limited basic accounting knowledge and the lack of adoption of digital financial tools. This Community Service (PkM) program aims to enhance the financial literacy and basic accounting skills of members of the Komunitas Sukses Berjamaah Indonesia (KSBI) through a practical-based training approach. The activity was conducted on November 30, 2024, by the Faculty of Economics and Business, Universitas Trisakti, involving 20 participants engaged in culinary, fashion, and printing businesses. The methods used included interactive lectures, group discussions, and hands-on practice in preparing simple cash-based financial statements. The effectiveness of the training was evaluated through pre- and post-tests consisting of ten questions covering five key aspects of accounting understanding. The results indicated a significant improvement, with the average score increasing from 41.25 in the pre-test to 87.75 in the post-test, representing a 112.7% improvement. Participants also demonstrated behavioral changes toward more disciplined financial recording and showed interest in adopting digital accounting applications. This program proved effective in improving financial literacy and professionalism among MSME actors and serves as a sustainable model for capacity building to strengthen the competitiveness of small and micro enterprises.